Comparative life cycle assessment of high-density polyethylene and glass reinforced epoxy pipes in Sharjah, United Arab Emirates - Abu Laila, Ibrahim; Seddiq, Anoushah; Shaban, Mazhd; Masri, Ahmad; Mortula, Md. Maruf; Atabay, Serter; Dhin, Lara (Frontiers in Sustainable Cities, 2025)
This study addresses the environmental impacts of a critical infrastructure, water distribution pipelines. In Sharjah’s expanding urban areas, selecting appropriate pipe materials is crucial for sustainable resource usage, as the impacts these resource-intensive pipelines have on the environment are significant during the entire pipe life cycle from manufacturing to disposal. This paper presents a comparative lifecycle assessment (LCA) of Glass Reinforced Plastic (GRP) and High-Density Polyethylene (HDPE) pipes by utilizing SimaPro software and Ecoinvent V3 database to evaluate the selected pipes’ environmental impacts across their entire lifecycle. The results show that the production phase of both pipes has the highest overall environmental impact, and reducing pipe diameters may significantly decrease these impacts. Results from HDPE pipes show higher impacts in climate change and fossil depletion categories, whereas GRP pipes show higher impacts in human toxicity and ozone depletion. However, overall, GRP pipes have a lower impact on human health, ecosystems, and resources. These insights can be used to aid decision-makers and governmental bodies, such as the Sharjah Electrical and Water Authority (SEWA), in making well-informed and strategic choices aligned with the 11th UN Sustainable Development Goal of fostering sustainable cities and communities, thus ultimately contributing towards reducing the harmful environmental impacts of water distribution systems. This LCA-based study contributes towards a more sustainable and environmentally friendly approach to water distribution system planning and management, with the ultimate aim of ensuring the longevity and health of urban infrastructures.